Responsible government, 1873-1878 - Johann F Preller (Social Anthropology, 2024)
On the.whole students ·of South Afripan history , have neglected to study our Constitutional development, and studie& on South African Constitutional Law are few and far between. It seems that the South African student has a greater liking for the more controversial subject . . of political history, while studies on.the economic and social aspects of our develop~ent are not wanting .. In preparing this -essay on ''Responsible Government" I acutely felt the lack of adequate and reliable secondary• authorities on South African Constitutional History and Law. !nevi tably I had to • fall back upon the hfographies " ' of the statesmen of th~ early 1870 8 • Here again I was • disappointed. Most of_ the biograp~ies were~ parte • accounts. A laudable exception I fti.Dd in Walker's "Life of Lord de Villiers". Mention, however, must be made of Mr. Kilpin's work on the early Parliamentary l:i.fe at the Cape .. Historians usually_ -pour vials of profess1.onal wratq on "popular works". Now it is true that both "The Romance· ; of a .Colonial Parliament and "The Old Cape House't con- . tain ·much. gossipy mater:i,al. Nevertheless, they both contain valuable material and views, not found. even in .the most "professional works"·• The "Ahnexuresn to both these little books are invaluable to the student of Colonial Constitutional History. Primary Sources exist in abundance·. I was, however, great~y disappointed at the despatches of both the Governor and the. Secretary of State for the Colonies, contained in the "Government House Records". (to be found in the Govern-· . ment Archives, Cape Town) inasmuch as they do not contain useful references to the working of' the Colonial Constitution • • (ii) • . The "Merriman Papers·" I found very interesting, though not so enlightening as I had hoped. I am deeply indebted t·o Mr. D. Varley, Librarian of the South African Public Library, Cape Town, for placing my request to read through such letters touclj.ing the working of the Constitution before the Board of Trustees of the Merriman Collection, and obtaining their permission to do so. ·The Cape Parliamentary Papers are to be found printed in the Annexures to the Votes and Proceedings of the House of Assembly and Legislative Council. Several of these sets are to be found in Cape Town. The Librarian of the Parliamentary Library kindly gave me permission to use the set stowed aw_ay in the basement of that Library. The Imperial Parliamentary Papers are to be found in the "Blue Books" relating to South African affairs. Here,· again, several complete sets exist. The set most ·easily ~ccessible to the public is to be found in the Government· Archives. As to the debates in Parliament. As a.tbofficial Hansard of these early years is lacking, I had to turn to newspaper reports. The most satisfactory reports I found in the Cape Argus . Recently, a very. valuable source of information has come to light in England.in the shape of Governor Barkly's private letters. (see, in this conn~~ion, the Johannesburg "St.ar", 12/8/4 3) The prevailing circumstances however, will prevent the South African s'tudent to see these letters for some time to come. In writing this essay I have assumed two things, e.g. that the reader is aware of the existence of freedom of speech in Parliament, granted by Act No. 1 of 1854, and . ' • (iii} secondly, that the only language recognised by the Constitution was English. Furthermore, this essay is concerned only with the most salient features of the working of Responsible Government into which I have entered. in some detail • .. . I am greatly indebted to,and take this opportunity of thanking, Messrs. Rooseboom and Louw of the House of Assembly, for tackling the unenviable task of typing the essay and thereafter proof-reading it for mistakes, grammatical and otherwise, in the typescript. I have made.use of certain abbreviations of which